Relationship Between The Level of Knowledge and Family Support With Self-Efficacy In Patients With Tuberculosis - Made Mahaguna Putra; Aditha Angga Pratama; Ni Putu Nila Adnyani (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2019)
Introduction: Tuberculosis is a disease whose transmission rates continue to increase. Tuberculosis treatment requires support from family, level knowledge and good self-efficacy because the minimum treatment period of 6 months makes TB clients need to be strengthened to be able to undergo complete treatment and successfully recover. The purpose of this study was to determine the relationship of the level of knowledge and family support with self-efficacy in tuberculosis patients at the Sawan I Community Health Center. Self-efficacy is an individual's belief in managing certain behaviors to achieve healing. Methods: This research is a correlation study with cross-sectional design. The samples used were 53 samples selected by nonprobability sampling with a purposive sampling design. The data collected through a questionnaire and obtained were tested with the Spearman rank test. From the correlation test with the Spearman rank test. Results: Correlation coefficient values indicate the relationship between knowledge and self-efficacy (r = 0.450) and family support with self-efficacy (r = 0.555), which means there is a strong and positive relationship or the better the level of knowledge and family support for TB sufferers, the better the self-efficacy of TB sufferers. Conclussions: The level of knowledge and family support are very important to maintain the self-efficacy of tuberculosis patients.